(untitled) (Research, Society and Development, 2023)
The objective of this work was evaluating the replacement of monensin and virginiamycin with essential oils and short-chain fatty acids on performance, dry matter intake, and ruminal fermentation in beef cattle fed a whole shelled corn-based diet. A total of 36 young bulls initially averaging 6 ± 2 months old and 257.2 ± 17.2 kg body weight (BW) were allotted to two treatments: 1) diet containing virginiamycin and monensin and 2) diet containing essential oils and short-chain fatty acids. The animals were adapted to the whole shelled corn-based diets by receiving 85% whole corn grain and 15% proteic-mineral pellet for 14 days. The experimental period was of 98 days. Performance, dry matter intake (% BW), feed-to-gain ratio, fecal pH, ruminal pH, and volatile fatty acids in the rumen fluid were assessed. The study was conducted using a completely randomized design. A difference was observed in the average daily gain (P<0.01). No significant differences were found in dry matter intake (% BW) and feed-to-gain ratio (P>0.05). Regarding volatile fatty acids in ruminal fluid, differences (P<0.01) were observed only for acetic acid. Except for the 22:00 h, differences (P<0.01) in ruminal pH were observed in all sampling times (06:00, 14:00, and overall). Therefore, replacing monensin and virginiamycin with essential oils and short-chain fatty acids in beef cattle fed a whole shelled corn-based diet was effective for performance without impairing ruminal fermentation, which could affect animal health.